The structure of financial systems and top incomes in advanced economies: A comparative distributional analysis of the financial wage premium - Anthony Roberts; Roy Kwon (Luxembourg Income Study (LIS), 2021)
Prior country case studies show substantial wage premiums in the financial sector contributes to growth of top incomes and wage inequality in a select group of advanced economies. However, while comparative studies show financialization exerts heterogenous effects on wage inequality across advanced economies, it is unclear whether the magnitude and location of financial wage premium in the distribution of income varies across advanced economies. We address this gap in the empirical literature by examining the financial wage premium across the labor income distributions of 13 advanced economies since the 1980s using harmonized labor force data from multiple waves of the Luxembourg Income Study. Consistent with prior studies, we find the financial wage premium is concentrated at the upper end of the income distribution in most advanced economies, but the magnitude of the premium substantially varies across these economies. We account for this variation by showing the market structure of financial systems exacerbates the financial wage premium at the upper end of the distribution. Overall, this study shows the financial wage premium is an important distributional mechanism for understanding the growth of top incomes and wage inequality in advanced economies and the marketization of financial activity amplifies the wage dynamics of financialization.
Keywords: 330; Financialization; Top Incomes; Wage Inequality; Economic Methodology; Comparative Sociology